Bread in archaeology - Samuel, Delwen (Institut de sociologie de l'Université Libre de Bruxelles, 2002)
This introductory article gives a history of the research on archaeological bread from the nineteenth century until recently. The different aspects that are relevant to adequate analyses and the correct interpretation of bread remains are discussed with a particular stress on future prospectives.